Habilidades sociais na comorbidade entre dificuldade de aprendizagem e problemas de comportamento : uma avaliação multimodal - Barreto, Simone de Oliveira (2007)
This study describes the repertoire of social skills and the frequency of externalizing and internalizing behavior problem among children who presented both problem behavior and learning disabilities. The children were evaluated using a variety of measures in social, behavioral and academic domains, using a multiple assessment method (different procedures, instruments and informants) as former reserch points out to a positive bias between children self-evaluation and teacher evaluation. The objectives of this investigation were: (1) characterize the social skills repertorie of children with comorbity of problem behaviors and learning disabilities; (2) characterize the frequency of externalizing and internalizing problem behaviors among these children; (3) compare The social skills self-evaluation to teacher s evaluation; (4) comparing results obtained using two differents instruments for social skills evaluation; (5) Identify the children s special needs, related to the frequency of externalizing and internalizing behavior problem and to deficits in their social skills repertorie. Paticipants were 50 children, 9 to 12 years of age, in the third on fourth grade classes of five elementary public schools, and their teachers, in a small city in the state of São Paulo, Brasil. Three instruments the IMHSC-Del-Prette (Del Prette & Del Prette, 2005), SSRS-BR (Bandeira, Del Prette, Del Prette & Magalhães, s.d.) and TDE (Stein, 1994)-were used to assess the children s social, behavioral and academic skills. Scores were determined according to instructions in each manual and these data were analysed using descripitive and inferential statistical methods. The results show that these children present deficits in their social skills repertorie, along with high frequency of externalizing and internalizing problems. There were biases between self-evaluation and teacher evaluation. This research concludes that children with comorbity of learning disabilities and problem behavior have special needs that are strongly related to their social and behavioral skills deficits.